Correlated patterns of genetic diversity and differentiation across an avian family. Issue 15 (27th March 2017) - Van Doren, Benjamin M.; Campagna, Leonardo; Helm, Barbara; Illera, Juan Carlos; Lovette, Irby J.; Liedvogel, Miriam
Abstract: Comparative studies of closely related taxa can provide insights into the evolutionary forces that shape genome evolution and the prevalence of convergent molecular evolution. We investigated patterns of genetic diversity and differentiation in stonechats (genus Saxicola ), a widely distributed avian species complex with phenotypic variation in plumage, morphology and migratory behaviour, to ask whether similar genomic regions have become differentiated in independent, but closely related, taxa. We used whole‐genome pooled sequencing of 262 individuals from five taxa and found that levels of genetic diversity and divergence are strongly correlated among different stonechat taxa. We then asked whether these patterns remain correlated at deeper evolutionary scales and found that homologous genomic regions have become differentiated in stonechats and the closely related Ficedula flycatchers. Such correlation across a range of evolutionary divergence and among phylogenetically independent comparisons suggests that similar processes may be driving the differentiation of these independently evolving lineages, which in turn may be the result of intrinsic properties of particular genomic regions (e.g. areas of low recombination). Consequently, studies employing genome scans to search for areas important for reproductive isolation or adaptation should account for corresponding regions of differentiation, as these regions may not necessarily represent speciation islands or evidence of local adaptation. Abstract : see also the Perspective by Burri